Application of Modified Cesarean Hysterectomy for Patients with Placenta Previa Complicated with Placenta Percreta - Yin Zhao; Li Zou; Hui Gao; Di Wu; Jian-Wen Zhu; Xiao-Xia Liu; Wen Zhang; Li-Bo Luo; Yang Pan; Dan-Dan Shi (Wolters Kluwer Health, 2020)
Abstract. Objective:. To evaluate the efficacy and safety of a modified cesarean hysterectomy (MCH) procedure in controlling hemorrhage in patients with placenta previa complicated with placenta percreta. Methods:. A retrospective analysis was conducted on 23 patients with placenta previa complicated with placenta percreta from January 2016 to December 2018 in the Union Hospital. The patients' age ranged from 24 to 41 years, and had gestational durations of 32-38 weeks. Nine of them underwent MCH and 14 underwent conventional cesarean hysterectomy (CCH). In the MCH group, the bladder was not mobilized, deliberately. The uterus was excised horizontally above the tourniquet level. Placental tissue around the cervical os was cleaned thoroughly, and hemostatic suturing was performed under direct vision. In the CCH group, the uterus was removed gradually after programmed hemostasis and dissection of adhesions of the vesicouterine peritoneal fold and mobilization of the bladder. Results:. There were no significant differences in general conditions between the two groups. The blood loss was significantly less in the MCH group (P < 0.05). The operation time was also decreased dramatically and hospital stay (in days) was shorter than in the CCH group (P < 0.05). There were no bladder or ureter injuries in the MCH group, compared with three cases in the CCH group. There were no statistically significant differences in neonatal birth weight, Apgar score, or intensive care unit admittance rates between the two groups (P > 0.05). Conclusion:. This MCH procedure reduced blood loss, avoided bladder injury, and had no long-term complications. It is a safe, rapid, and effective way to control fetal hemorrhage during surgery for women with placenta previa complicated with placenta percreta.